PROSPECTS FOR IMPROVING THE QUALITY OF CORPORATE GOVERNANCE IN JOINT-STOCK COMPANIES - Yuldashova Gavkhar Khusnitdinovna (American Journals, 2025)
In modern conditions of economic development, one of the important conditions for the functioning and innovative development of companies is an effective management system. The stability and competitiveness of existing companies directly depends on their management. Well-established corporate governance, in turn, affects the company's position in the market, the level of its modernization, digitalization and directly the standard of living of the company's employees. Today, it is considered important to organize an economically effective and scientifically sound way of assessing the quality of company management, as well as systematic work to improve the management system.
Keywords: Corporate governance, efficiency, enterprise goals, production, innovation, companies, Supervisory Board, competitiveness, quality of management.